2018
DOI: 10.4103/ijccm.ijccm_156_18
|View full text |Cite
|
Sign up to set email alerts
|

Non- Neurological Complications after Traumatic Brain Injury: A Prospective Observational Study

Abstract: Introduction and Aims:Recognizing and treating nonneurological complications occurring in traumatic brain injury (TBI) patients during intensive care unit (ICU) stay are challenging. The aim is to estimate various nonneurological complications in TBI patients. The secondary aim is to see the effect of these complications on ICU stay, disability, and mortality.Materials and Methods:This was a prospective observational study at the neuro-ICU of a Level-I trauma center. A total of 154 TBI patients were enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Patients with severe TBI often become septic and succumb to multiple organ dysfunction syndrome (16). Organs most frequently affected include the lung (17), kidneys (18), and the gut (15,19). The role of the gut in post-hemorrhagic shock multiple organ failure was identified over two decades ago (20).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe TBI often become septic and succumb to multiple organ dysfunction syndrome (16). Organs most frequently affected include the lung (17), kidneys (18), and the gut (15,19). The role of the gut in post-hemorrhagic shock multiple organ failure was identified over two decades ago (20).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of TBI was stratified by grouping the research patients according to GCS score [3][4][5][6][7][8][11][12][13][14][15][16][17], mean AIS head score, the number of pack cell units transfused in the first 24 hours of hospitalization, the type of treatment (surgery or conservative treatment), the type of airway management (intubation or nonintubation), the duration of hospitalization, and GCS at the time of discharge, as well as the patient outcome as improvement or in-hospital death was assessed and recorded. The diagnosis of ALI was based on the International Consensus Criteria per PaO2/FiO2 ratio on the first and third days.…”
Section: Methods and Materials/patientsmentioning
confidence: 99%
“…Moreover, this complication being an independent predictor factor for poor prognosis. This data discrepancy was caused by differences in the inclusion criteria; regardless of these differences, all of these studies reported that the presence of ALI/ARDS was associated with increased mortality and morbidity in patients with severe brain injury [11][12][13][14][15][16][17][18]. It was also associated…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical presentation of NPE is thought to range from subclinical to fulminant pulmonary edema. Meningeal haemorrhage is thought to be one of the most common causes of neurogenic pulmonary edema [2]. We present a case of a 23-year-old female who presented with traumatic brain injury (TBI) and within hours developed neurogenic pulmonary edema.…”
Section: Introductionmentioning
confidence: 99%